What are the diagnostic criteria for interstitial cystitis?. Issue 11 (November 2017) - Brits, Ferdinand; Collins, Rebecca
Abstract : EVIDENCE‐BASED ANSWER : Interstitial cystitis may be diagnosed by the more restrictive criteria of the National Institute of Diabetes, Digestive, and Kidney (NIDDK), which requires bladder pain or urinary urgency for 9 months, the presence of glomerulations or Hunner's ulcer on cystoscopy, and urodynamic evaluation. The NIDDK criteria exclude more than 50% of patients who clinicians suspect have interstitial cystitis based on the more inclusive criteria of urinary frequency (≥7 times per day), urgency, or bladder pain for at least 6 months with no other clear etiologies (SOR: B, cross‐sectional study). The most common symptoms of interstitial cystitis include urgency, frequency, nocturia, pain in the bladder, pain in the urethra, and pain in the vagina (SOR: B, systematic review of cross‐sectional studies). Experts characterize interstitial cystitis as an unpleasant sensation (pain, pressure, discomfort) thought to be related to the urinary bladder and associated with lower urinary tract symptoms of more than 6 weeks' duration, in the absence of infection or other identifiable causes (SOR: C, expert opinion).